Comparison of outcomes between laparoscopic ureterolithotomy and push back PCNL in the management of upper ureteric stone - Alam, Md Naushad; Alam, Md Shawkat; Islam, Khan Nazrul; Miah, Md Latifur Rahman (Bangladesh Journal of Urology, 2023)
Background: Upper ureteral stones are a common issue. There are numerous treatment options available, including medical expulsive therapy, shockwave lithotripsy, ureteroscopic stone extraction, PCNL and laparoscopic ureterolithotomy. PCNL and laparoscopic ureterolithotomy are the main approaches for large upper ureteral stones. Objective: To compare the outcome between laparoscopic ureterolithotomy and push back PCNL in the management of upper ureteric stone Methods: In this prospective study 60 patients presenting with upper ureteric stone were selected. Patients with renal insufficiency (creatinine >2.5 mg/dL), morbid obesity, coagulopathy, concurrent renal and ureteric stones, pregnancy, sepsis, stone size more than 30 mm, orthopedic contraindications for prone position and those with a probability of inability to achieve safe access to the collecting system on pre-operative imaging were excluded from this study. Upper ureteric stones were removed from 30 patients by laparoscopic ureterolithotomy and by push back PCNL procedure from another 30 patient stones. Two procedures were compared based on stone clearance rate, complications, surgery time and postoperative hospital stay. Results: The mean age of the laparoscopic ureterolithotomy group in this study was 41.83 ± 7.96 years and in push back PCNL group it was 42.23 ± 7.42 years (p = 0.841). Male patients were predominant than female patients in each group. Mean stone diameter of laparoscopic ureterolithotomy group was 22.90 ± 4.18 mm and in push back PCNL group it was 21.26 ± 3.85 mm (p=0.122). Mean operative time of laparoscopic ureterolithotromy patients was 1.42 ± 0.14 hours and in push back PCNL group it was 1.19 ± 0.09 hours, the difference between the procedures was statistically significant (p<0.001). In laparoscopic ureterolithotomy group postoperative prolonged urine leakage was found in 4 (13.3%) cases and postoperative fever in 1 (3.3%) case. Postoperative analgesic required in 6 (20.0%) cases in laparoscopic ureterolithotomy group and 7 (23.3%) cases in push back PCNL group. Transfusion required only in push back PCNL group (13.3%). Duration of post-operative hospital stay was significantly higher in laparoscopic ureterolithotromy group than push back PCNL group. In this study, stone clearance rate was 100.0% & 100.0% in both the groups. Conclusion: Both laparoscopic ureterolithotomy and push back PCNL are similar in management of upper ureteric stone. Bangladesh J. Urol. 2022; 25(1): 14-18